Analisis Trading Volume Activity dan Bid-Ask Spread Setelah Stock Split - Ade Wahyu Merthadiyanti, Luh; Wirawan Yasa, Gerianta (E-Jurnal Akuntansi, 2019)
This study aims to determine whether there is an increase in TVA and a decrease in the bid-ask spread after a stock split is carried out. The population in this study were all companies on the IDX that conducted a stock split in which there were 234 companies. The number of samples taken was 53 companies, with non probability sampling methods, specifically purposive sampling. Data collection techniques are documentation techniques from the Indonesia Stock Exchange. The analytical method used is the analysis of paired sample t-test. Based on the results of the analysis it was found that there was an increase in TVA after the stock split which showed that investor interest had increased due to low stock prices and a decrease in bid-ask spreads which showed that stock trading liquidity had increased. Keywords: Trading volume, bid-ask, split